2019
DOI: 10.1111/hepr.13426
|View full text |Cite
|
Sign up to set email alerts
|

Rapid increase of platelet counts during antiviral therapy in patients with hepatitis C virus infection

Abstract: The cause of thrombocytopenia in patients with chronic hepatitis C virus (HCV) infection is multifactorial: hypersplenism, decreased thrombopoietin levels, and myelosuppression induced by HCV. Platelet counts increase after eradication of HCV; however, this mechanism is not fully understood. Therefore, the aim of this study was to determine the influence of these three factors on platelet counts. Methods:We retrospectively analyzed data from 109 HCVinfected patients with platelet counts ≤150 × 10 3 /μL who ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
0
12
5
Order By: Relevance
“…30 The clinical trial was demonstrated that the cause of thrombocytopenia in patients with chronic hepatitis C virus (HCV) infection, which was possibly caused by improvement of hypersplenism and HCV-induced bone marrow toxicity resulting from anti-HCV therapy. 31 Acute dermatitis and oral mucositis of the two groups were not obvious different in our study. This may have been because of strictly controlled other variables between radiation techniques.…”
Section: Discussioncontrasting
confidence: 43%
“…30 The clinical trial was demonstrated that the cause of thrombocytopenia in patients with chronic hepatitis C virus (HCV) infection, which was possibly caused by improvement of hypersplenism and HCV-induced bone marrow toxicity resulting from anti-HCV therapy. 31 Acute dermatitis and oral mucositis of the two groups were not obvious different in our study. This may have been because of strictly controlled other variables between radiation techniques.…”
Section: Discussioncontrasting
confidence: 43%
“…reported that an SVR can increase the platelet count by reducing the splenic volume (21). However, the mean splenic volume did not decrease, even after the achievement of an SVR in the present study.…”
Section: Discussioncontrasting
confidence: 87%
“…This discrepancy may have been due to the difference in the splenic volume at baseline. The medians splenic volume in the present study was 634 ml, while that in Ishizu's study was 242 ml (21). Thus, other mechanisms accounted for the increased platelet count in group B patients who received repeated treatment.…”
Section: Discussioncontrasting
confidence: 55%
“…Under this, IMRT had possessed a more homogenous dose distribution, which was reported as a good alternative to treat cervix carcinoma with bone marrow toxicity [30]. The clinical trial was demonstrated that the cause of thrombocytopenia in patients with chronic hepatitis C virus (HCV) infection, which was possibly caused by improvement of hypersplenism and HCV-induced bone marrow toxicity resulting from anti-HCV therapy [31]. Acute dermatitis and oral mucositis of the two groups were not obvious different in our study.…”
Section: Discussionmentioning
confidence: 99%